A prospective randomized study to compare hemodynamic changes and post-operative outcome of intravenous buprenorphine versus epidural buprenorphine in patients undergoing abdominal surgeries under general anesthesia - Youvaraj M; Jitendra Agrawal; Brajesh Kumar; Sourabh Shrivastava; Preeti Goyal (Asian Journal of Medical Sciences, 2023)
Background: Post-operative pain following major abdominal surgeries is accompanied with multitude of negative consequences, including increased morbidity, impaired physical function, and slow recovery. Opioids are the gold standard of post-operative pain management. Buprenorphine is a new semi-synthetic opioid and 0.3 mg has shown equipotent effect as 12.5 mg of morphine and 0.125 mg of fentanyl.